The Impact of Labor Market Reforms on Capital Flows, Wages and Unemployment - Thomas Beissinger (Institute for the Study of Labor (IZA), 2001)
The paper contributes to the globalization debate by scrutinizing the international spillover effects which are provoked if a single country reduces the generosity of the unemployment compensation system or weakens labor union power. For this purpose a two-country model with imperfect competition in goods and labor markets and perfect competition in capital markets is developed. It is demonstrated that the comparative-static results depend on the degree of capital mobility, the degree of competition in the goods market and the institutional setup of the unemployment compensation system. Furthermore, it is shown that the impact of country-specific labor market reforms on households in other countries depends on whether the household's main income source consists of wage income or capital income and profits.
Keywords: E24; F21; J65; F41; J51; J23; 330; Globalization; capital mobility; unemployment; unemployment compensation; wage bargaining; monopolistic competition; welfare state; Arbeitsmarktflexibilisierung; Lohn; Beschäftigungseffekt; Spillover-Effekt; international; Zwei-Länder-Modell; Internationale Kapitalmobilität; Arbeitslosenversicherung; Lohnverhandlungstheorie; Theorie